The Ming prince and Daoism institutional patronage of an elite - Wang, Richard G. (Oxford [u.a.] Oxford University Press, 2012)
Ming princes: an overview -- Princely ritual institutions -- Ming princes and Daoist ritual -- Cultivation and book -- Temple patronage -- Literary patronage -- Princely contacts with clerics and fashion of Daoist names -- Multi-faceted princely patronage of a Daoist temple -- Genealogical chart of the Ming emperors and their lines of descent -- Numbers of princes under each emperor
Ming princes: an overview -- Princely ritual institutions -- Ming princes and Daoist ritual -- Cultivation and book -- Temple patronage -- Literary patronage -- Princely contacts with clerics and fashion of Daoist names -- Multi-faceted princely patronage of a Daoist temple -- Genealogical chart of the Ming emperors and their lines of descent -- Numbers of princes under each emperor.
Includes bibliographical references (p. 253-291) and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Taoism and state -- China -- History; Princes -- Religious life -- China -- History; Taoism and state -- China -- History; Princes -- Religious life -- China -- History